Relation Between Serum Sodium Trajectory and Survival in Septic Patients with Cardiopulmonary Bypass Surgery: Based on Medical Information Mart for Intensive Care-IV Database - Zhiying Shen; Bo Yang; Guiyu Cai; Lugang Mei; Yang Wu; Xuefei Yu (Journal of Investigative Surgery)
Objective The influence of serum sodium level changes on septic patient survival after cardiopulmonary bypass surgery is not clear. We attempted to figure out the impact of serum sodium trajectory changes on the 30-day mortality rate of such patients.Methods The Medical Information Mart for Intensive Care (MIMIC)-IV database was searched to gather patients who developed sepsis after cardiopulmonary bypass surgery. A group-based trajectory model (GBTM) was employed to determine the serum sodium trajectory within 72 h of ICU admission. Patients’ survival differences between different trajectory groups were compared using Kaplan–Meier (K–M) survival curves. Cox regression models were further employed to explore the correlation between survival status and serum sodium trajectory.Results 1,038 eligible patients were involved in this project. GBTM identified 3 serum sodium trajectories, all showing a trend of initial decrease followed by an increase. K–M curve analysis uncovered a notable difference in 30-day survival status between Class 1 and Class 2 (Log-rank p = 0.039), while no obvious differences were observed between other groups. Cox hazard analysis revealed that in the three models adjusting for different covariates, Class 2 was connected with the increased risk of survival (OR > 1, p < 0.05).Conclusion Higher serum sodium trajectory is linked with elevated 30-day death risk in septic patients following cardiopulmonary bypass surgery. Repressing high levels of serum sodium may be beneficial for patient survival.